The TGFβ1 Promoter SNP C-509T and Food Sensitization Promote Esophageal Remodeling in Pediatric Eosinophilic Esophagitis. - Renee Rawson; Arjun Anilkumar; Robert O Newbury; Vineet Bafna; Melissa Aquino; Jacob Palmquist; Hal M Hoffman; James L Mueller; Ranjan Dohil; David H Broide; Seema S Aceves (PLoS ONE, 2015)
Background Eosinophilic esophagitis (EoE) is a chronic antigen mediated disease associated with substantial esophageal remodeling and fibrosis. The functional TGFβ1 promoter SNP C-509 associates with renal fibrosis and asthma. The effect of TGFβ1 genotype and EoE severity or potential gene-environment interactions have not been previously reported in EoE. Methods Genotype at TGFβ1 C-509T and remodeling was analyzed in 144 subjects with EoE. The severity of remodeling and inflammation was analyzed in the context of IgE sensitization to food antigens and C-509T genotype. Results The TGFβ1 promoter C-509 genotypes CC, CT, and TT were 35%, 52%, and 13%, respectively. Sixty-six percent of subjects were sensitized to foods by positive skin prick test (SPT) or serum specific IgE. TT genotype subjects had significantly more TGFβ1 (CC subjects = 1300 per mm2; TT = 2250 per mm2) (p<0.05) and tryptase (CC subjects = 145 per mm2: TT = 307 per mm2) (p<0.05) positive cells and higher epithelial remodeling scores (2.4 vs 3.7, p<0.001) than CC subjects. The differences in TGFβ1 and tryptase positive cells as well as fibrosis were significantly increased when there was concurrent food sensitization. Food sensitization alone did not associate with any parameters of inflammation or remodeling. Conclusions Our data support a gene-environment interaction between food and genotype at C-509 that modulates disease severity in EoE. Since EoE subjects often continue to consume foods to which they are sensitized, these findings may have clinical relevance for disease management.